STUDI KASUS: PENGARUH GRATITUDE THERAPY TERHADAP PENURUNAN SIMTOM DEPRESI PADA PEREMPUAN YANG HAMIL DI LUAR NIKAH - Novensia Wongpy; Hartanti Hartanti; Ktut Dianovinina (Perpustakaan Universitas Surabaya, 2018)
The purpose of this study is to find out the effect of Gratitude Therapy in reducing symptoms of depression in pregnant women out of wedlock. This research used the method called “mixed method” with combining quantitative method which was single case experiment and quantitative method which was case study. This study used a single subject woman suffering from depression due to pregnancy out of wedlock, then married but split up and currently the sole mother of two children. Depression is measured by using Beck Depression Inventory (BDI) and the results shows that the subject is experiencing mild depression. Gratitude Therapy is given to the subject with 8 sessions and approximately 5 weeks. The result of the intervention shows the depression is decreasing from mild depression to does not show any depression symptom. The decrease happens in emotional symptom, cognitive symptom and physical symptom. Grati tude can change the subject’s point of view from negative thoughts and emotions that cause more depression to positive thoughtsin life so that the subject's thoughts and emotions are more positive and the symptoms of dep ression are felt to be decreasing. Qualitative results also show the subject does not feel the symptoms of depression and has been able to take the positives of the problems that occur in life.